Colonization with enterotoxigenic Bacteroides fragilis is associated with early-stage colorectal neoplasia. - Rachel V Purcell; John Pearson; Alan Aitchison; Liane Dixon; Frank A Frizelle; Jacqueline I Keenan (PLoS ONE)
Background Enterotoxigenic Bacteroides fragilis (ETBF) is a toxin-producing bacteria thought to possibly promote colorectal carcinogenesis by modulating the mucosal immune response and inducing epithelial cell changes. Here, we aim to examine the association of colonic mucosal colonization with ETBF and the presence of a range of lesions on the colonic neoplastic spectrum. Methods Mucosal tissue from up to four different colonic sites was obtained from a consecutive series of 150 patients referred for colonoscopy. The presence and relative abundance of the B. fragilis toxin gene (bft) in each tissue sample was determined using quantitative PCR, and associations with clinicopathological characteristics were analysed. Findings We found a high concordance of ETBF between different colonic sites (86%). Univariate analysis showed statistically significant associations between ETBF positivity and the presence of low-grade dysplasia (LGD), tubular adenomas (TA), and serrated polyps (P-values of 0.007, 0.027, and 0.007, respectively). A higher relative abundance of ETBF was significantly associated with LGD and TA (P-values of < 0.0001 and 0.025, respectively). Increased ETBF positivity and abundance was also associated with left-sided biopsies, compared to those from the right side of the colon. Conclusion Our results showing association of ETBF positivity and increased abundance with early-stage carcinogenic lesions underlines its importance in the development of colorectal cancer, and we suggest that detection of ETBF may be a potential marker of early colorectal carcinogenesis.